Anti-inflammatory effect of triptolide - Zheng You-lan; Lin Jian-feng; Lin Cheng-cai; Xu Ya (Acta Pharmacologica Sinica; Vol 15, No 6 (November 1994): Acta Pharmacologica Sinica, 2016)
Triptolide (Tri) was isolated from Tripterygium wilfordii Hook f. Tri 0.1-0.2 mg.kg-1 sc or 0.15-0.3 mg.kg-1 ig inhibited markedly the increased vascular permeability induced by ip 0.7% HAc in mice. Tri 0.05-0.1 mg.kg-1 ip or 0.15-0.3 mg.kg-1 ig inhibited hind paws swelling induced by sc 0.15 ml carrageenan and also inhibited the same swelling induced by sc 2.5% formaldehyde 0.1 ml in rats. Tri 0.05-0.1 mg.kg-1 ip inhibited markedly proliferation of granuloma induced by sc implantation of cotton-pellets in rats, but 0.2 mg.kg-1 ip can not inhibit the same swelling induced by sc 0.15 ml carrageenan in adrenalectomized rats. Tri 0.2 mg.kg-1 ip decreased markedly weight of thymus. Tri 0.2 mg.kg-1 ip, but 0.1 mg.kg-1 ip did not reduced the content of ascorbic acid of adrenal gland in rats. Tri 0.2 mg.kg-1 ip did not decrease the pro-staglandin E content in inflammatory tissues. These results indicate that high dose of Tri can stimulate the pituitary-adrenal axis.